2012
DOI: 10.1007/s11102-012-0407-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, timing of peak responses and safety aspects of two dosing regimens of the glucagon stimulation test in evaluating growth hormone and cortisol secretion in adults

Abstract: Weight-based (WB: 0.03 mg/kg) and fixed dose (FD: 1-1.5 mg) regimens of the glucagon stimulation test (GST) have been used to evaluate GH and cortisol secretion in children and adults, respectively. However, experience of the WB regimen in assessing GH and cortisol secretion in adults are limited. We describe a multicenter experience using WB and FD regimens in evaluating GH and cortisol secretion in adults suspected of GH deficiency and central adrenal insufficiency. Retrospective case series of GSTs (n = 515… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
1
28
2
Order By: Relevance
“…32 In this study, we found that peak and nadir glucose, and delta GH, were higher in the weight-based regimen. In both regimens, BMI, fasting, peak, and nadir glucose correlated negatively with peak GH levels.…”
Section: Future Perspectivesmentioning
confidence: 54%
See 2 more Smart Citations
“…32 In this study, we found that peak and nadir glucose, and delta GH, were higher in the weight-based regimen. In both regimens, BMI, fasting, peak, and nadir glucose correlated negatively with peak GH levels.…”
Section: Future Perspectivesmentioning
confidence: 54%
“…To address this question, we evaluated GSTs performed in 515 patients, and found that BMI, fasting, peak, and nadir glucose levels correlated negatively with peak GH levels. 32 These data therefore suggest that lower GH cutpoints may be needed if the GST is to be used to reliably evaluate the GH reserve in hyperglycemic overweight/ obese patients, but requires further confirmation with larger prospective studies. This is clinically relevant because performing ITT in patients with diabetes and/or obesity can be challenging and may not be safe especially as large insulin doses are usually required to induce symptomatic hypoglycemia in these patients with underlying insulin resistance.…”
Section: Historical Perspective Of the Use Of Glucagon Stimulation Tementioning
confidence: 88%
See 1 more Smart Citation
“…The GST was initially described as a 4-h test, but subsequent studies reduced the procedure time for 3 h, claiming that the majority of GH peaks occur between 120 and 180 min [9,10]. However, GH peaks after 3 h have been observed in up to one-third of patients in different studies, challenging the suggestion to shorten the procedure [11][12][13][14]. GST is usually performed with a fixed-dose of 1 mg (or 1.5 mg in patients over 90 kg) of glucagon administered via subcutaneous or intramuscular route [5,6,[10][11][12][13][14].…”
mentioning
confidence: 99%
“…However, GH peaks after 3 h have been observed in up to one-third of patients in different studies, challenging the suggestion to shorten the procedure [11][12][13][14]. GST is usually performed with a fixed-dose of 1 mg (or 1.5 mg in patients over 90 kg) of glucagon administered via subcutaneous or intramuscular route [5,6,[10][11][12][13][14]. Weight-based doses of glucagon in adults have been shown to promote higher cortisol and GH responses than fixed doses, resulting in different cutoff points for diagnosing SAI and GHD [13,14].…”
mentioning
confidence: 99%